Financial Reporting Strategies for SMEs to Support Bank Credit Applications - Triwibowo, Edi; Fuadi, Agus; Wulandari, Dian Sulistyorini; Widiyaningsih, Widiyaningsih (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service program aimed to enhance the financial literacy of small and medium-sized enterprises (SMEs) in South Tambun, enabling them to prepare accurate financial reports required for bank loan applications. The program provided a series of training workshops, hands-on exercises, and personalized consultations, focusing on the preparation of income statements, balance sheets, and cash flow statements. A total of 8 business owners from various industries participated in the program. The results indicated a significant improvement in participants' understanding of financial reporting, with 87.5% of participants reporting increased confidence in their financial management skills. Additionally, 75% of participants felt prepared to apply for bank loans with the reports they had created. The program demonstrated the value of practical training in improving the financial capabilities of SMEs and facilitating their access to formal financial services. Based on the outcomes, recommendations for further support, advanced training, and partnerships with financial institutions are provided to ensure the sustainability and expansion of the program's impact.